2010
DOI: 10.1093/toxsci/kfq263
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Hexavalent Chromium Resulted in Significantly Higher Tissue Chromium Burden Compared With Trivalent Chromium Following Similar Oral Doses to Male F344/N Rats and Female B6C3F1 Mice

Abstract: In National Toxicology Program 2-year studies, hexavalent chromium [Cr(VI)] administered in drinking water was clearly carcinogenic in male and female rats and mice, resulting in small intestine epithelial neoplasms in mice at a dose equivalent to or within an order of magnitude of human doses that could result from consumption of chromium-contaminated drinking water, assuming that dose scales by body weight(3/4) (body weight raised to the 3/4 power). In contrast, exposure to trivalent chromium [Cr(III)] at mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Because of that, attention has been focused on the toxic action of Cr(VI), since it is highly hepatotoxic (Rafael et al, 2007) and nephrotoxic (Khan et al, 2010;Molina-Jijón et al, 2011). Moreover, certain studies have indicated that this metal accumulates in the liver and kidneys (Sutherland et al, 2000;O'Brien et al, 2003;Collins et al, 2010;Chang et al, 2011), corroborating the results found here. However, the mice pretreated with the 25 and 50 mg/kg doses of PGE showed an interesting change in the bioavailability of FIGURE 3 -Survival analysis of animals prophylactically t r e a t e d w i t h d i f f e r e n t P G E d o s e s ( 2 5 , 5 0 a n d 75 mg/kg/day) for 10 days and exposed to a lethal dose of Cr(VI) (50 mg/kg) on the 11 th day.…”
Section: Discussionsupporting
confidence: 86%
“…Because of that, attention has been focused on the toxic action of Cr(VI), since it is highly hepatotoxic (Rafael et al, 2007) and nephrotoxic (Khan et al, 2010;Molina-Jijón et al, 2011). Moreover, certain studies have indicated that this metal accumulates in the liver and kidneys (Sutherland et al, 2000;O'Brien et al, 2003;Collins et al, 2010;Chang et al, 2011), corroborating the results found here. However, the mice pretreated with the 25 and 50 mg/kg doses of PGE showed an interesting change in the bioavailability of FIGURE 3 -Survival analysis of animals prophylactically t r e a t e d w i t h d i f f e r e n t P G E d o s e s ( 2 5 , 5 0 a n d 75 mg/kg/day) for 10 days and exposed to a lethal dose of Cr(VI) (50 mg/kg) on the 11 th day.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with data by Kirman et al (2012), which found concentrations of total chromium in the small intestine to be higher in mice than in rats when administered equivalent concentrations of Cr6 in drinking water for 90 days. The NTP studies found that stomach and liver tissue concentrations (when normalized by average dose) were higher in mice than in rats (Collins et al, 2010), which is also consistent with reduction in the mouse stomach being less efficient.…”
Section: Analysis Of Stomach Reductionsupporting
confidence: 62%
“…Following in vivo studies in rodents, mice were found to have accumulated more chromium than rats Collins et al, 2010). This may indicate more effective absorption and/or less effective Cr6 reduction in the mouse.…”
Section: Introductionmentioning
confidence: 99%
“…However, others argue that the reduction of Cr(VI) to Cr(III) outside of cells and absorption of Cr(VI) by cells via non-specific anion transporters occur almost simultaneously and both processes compete with each other for substrate [12,61]. This competition combined with other factors including gastric emptying time, food content, and interspecies difference in reduction, result in a portion of ingested Cr(VI) (10–20%) escaping gastric detoxification and being absorbed into cells of target tissues even at very low concentrations [12,61], This fact was well supported by the tissue distribution analysis of ingested Cr(VI) in both human and animal studies [3234]. However, many questions still need to be addressed, including the reduction capacity of gastric fluid, the rates and capacities for Cr(VI) reduction along the GI tract, the rate of Cr(VI) absorption in the GI tract, and the factors that potentially affect Cr(VI) reduction or absorption.…”
Section: Mechanisms Of Chromium Toxicity and Carcinogenicitymentioning
confidence: 96%